ANALYSIS OF THE EFFECTIVENESS OF IDENTITY CARD (KTP) SERVICES AT THE PANJANG DISTRICT OFFICE, BANDAR LAMPUNG CITY - Alfian Malik; M. Oktavianur (International Journal of Multidisciplinary Reseach, 2026)
This study used a descriptive qualitative research method. The method was applied to describe and qualitatively examine the effectiveness of Identity Card (KTP) services at the Panjang District Office, Bandar Lampung City. All data were obtained directly from field informants through interviews and document studies. The findings show that: (1) in the time-unit dimension, KTP services still experience several obstacles, such as delays in the service process caused by disruptions to the population administration system network and limited supporting service facilities; (2) in the output-unit dimension, KTP services have been able to produce population documents for the community, but several obstacles remain, such as administrative data errors and delays in printing electronic ID cards; and (3) in the work-quality dimension, officials at Panjang District generally provide services quite well and in a friendly manner. The inhibiting aspects include delays due to the limited number of employees and network disruptions, data errors and printing delays, non-optimal achievement of service targets, and the less-than-optimal capability and professionalism of service officials.